Instrumentos de promoción de los vinos en los restaurantes de alto nivel - Irene Gil Saura; Gloria Berenguer Contrí; M. E. Ruiz Molina (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2009)
In recent years, wine marketing is assuming an increasingly important role in restaurants. The growing complexity of the supply of wines determines that consumer choice is conditioned by wine labels included in the wine list and the influence of the waiter. The objective of this study is to identify and characterize the relevant instruments for wine promotion used by restaurants, depending on the presence of wine specialists on staff. As a result of a study conducted among a sample of upscale restaurants, we note that the content and design of the wine list is largely conditioned by the presence of a sommelier, being both basic tools for promoting wines in the restaurant.
Keywords: 330; promotion; wine; hospitality